Micro flap technique: a novel approach for the management of a large epiglottic cyst - Prasad, K. C.; Gopinath, indu Varsha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Epiglottic cyst is a not an unusual disease in the larynx. Although the lesion is benign, airway obstruction may occur due to a large cyst both in children and adults. Therefore it should to be kept in mind in the differential diagnosis of stridor or difficulty in breathing. Common treatment modalities in dealing with these epiglottic cysts are endoscopic excision, marsupialization and even external approaches through neck in cases of very large cysts, complete Excision is usually the treatment of choice, with low recurrence. We report a case of a 38 years old man who presented with progressive difficulty in breathing, foreign body sensation and difficulty to swallow and the cyst was completely excised by s new micro flap technique, using both endoscope and microscope. The new method of excision of cyst after elevating the micro flaps and redraping on the raw surface causes faster healing process, less post operative edema and less post operative symptoms. The patient was discharged third day after the surgery without any complications.